Information Transfer in Logistics Using Wireless Technologies - Wieczorek, Adam (Olsztyn Economic Journal, 2020)
The aim of the study was to indicate by the author the possibility of using wireless technologies as part of improving information transfer, with particular reference to activities in the field of logistics. The article is a review in which the theoretical aspects of logistics and information logistics are highlighted. A review and analysis of domestic and foreign literature was used as the theoretical scope. To determine the examples of the use of appropriate technologies in information logistics, an Internet database was used as the source of enterprises presenting selected technologies. The author focused on 5 main technological aspects used in information transfer in logistics, such as: short-range technologies, local networks, wide-area networks, low power wide-area networks and global computer networks. The analysed application allowed conclusions to be drawn clearly indicating that the use of appropriate wireless technologies allows for a more effective provision of appropriate information resources in logistics.